Clinicopathological study of granulomatous lobular mastitis - Goel, Sapna; Goel, Kanwar Singh (International Surgery Journal, 2019)
Background: Granulomatous lobular mastitis is an uncommon disease. This condition may resemble malignancy and tuberculosis. It is characterised by granulomatous inflammation with multinucleated giant cells, epithelioid histiocytes. The inflammation is centred on lobules. The purpose of this study is to review the clinical and pathological aspects in 8 cases of granulomatous lobular mastitis and review of pertinent literature. Methods: This is a prospective observational study. A total of 8 patients were studied. Investigations done. Patient were treated by erythromycin 250mg qid, tinidazole 500mg bid, for 7 days and steroids for two months. The lumps were excised, sinuses were excised and abscesses were drained, and oral steroids were given. Follow-up was done for 6 months. Results: Most of the patients were multiparous and lactating, with age range from 18 to 36 years. Clinically the lesion was felt as malignant in 3 patients and benign in 5 patients. Most patients were using contraceptive pills. There was suppuration in 3 patients and sinuses were found in 2 patients. Histopathological examination revealed granulomatous inflammation centred on lobules. Conclusions: The diagnosis of granulomatous lobular mastitis should be made very carefully to avoid any confusion with malignancy, tuberculosis, fungal infection, sarcoidosis, mammary duct ectasia, cystic changes in breast with over palpation and puerperal mastitis with over palpation. Though it is rare disease, but complete understanding by pathologist and surgeon is required for improving its identification.